Lightweight Polymer Composite Structures : Design and Manufacturing Techniques - Rangappa, Sanjay Mavinkere, editor 642046; Parameswaranpillai, Jyotishkumar, editor 642047; Siengchin, Suchart, editor 642050; Kroll, Lothar, editor 642455 (Boca Raton, FL : CRC Press, 2020)
"The book provides a comprehensive account of developments in the area of lightweight polymer composites. It encompasses design and manufacturing methods for the lightweight polymer structures, various techniques and a broad spectrum of applications. The book highlights fundamental research in lightweight polymer structures and integrate various aspects from synthesis to applications of these materials. Current status, trends, future directions, and opportunities are discussed, making it friendly for both new and experienced researchers"--